ND AND SR ISOTOPES FROM DIAMONDIFEROUS ECLOGITES, UDACHNAYA KIMBERLITE PIPE, YAKUTIA, SIBERIA: EVIDENCE OF DIFFERENTIATION IN THE EARLY EARTH? - Snyder G.A.; Jerde E.A.; Taylor L.A.; Halliday A.N.; Sobolev V.N.; Sobolev N.V. (My University, 1993)
Nd and Sr isotopic data from diamond-bearing eclogites found in the Udachnaya kimberlite, Yakutia, Siberia, are interpreted as indicating an early (⩾ 4 Ga) differentiation event, whereby the mantle split into complementary depleted and enriched reservoirs. Reconstructed whole-rock87Sr/86Sr ratios (present-day) range from 0.70151 to 0.70315 and are consistent with a mantle origin for these rocks. The Nd isotopic evolution lines of four samples (U-5, U-37, U-41 and U-79) converge at 2.2–2.7 Ga. Sample U-5 is unique in exhibiting the most enriched signature of any of the samples yet analyzed (present-dayεNd of −20), and this sample points unequivocally to an old, enriched component. A complementary depleted mantle component is suggested by two of the eclogite samples, U-86 and U-25, which yieldεNd values (at 2.2 Ga) of + 13 and + 7, respectively. The two mantle reservoirs possibly formed prior to 4 Ga and evolved separately until 2.2–2.7 Ga. At that time, the reservoirs were melted forming eclogites both as residues (from the enriched reservoir) and as partial melts of peridotite (from the depleted reservoir), resulting in demonstrably different histories for eclogites from the same locality.